Relationship Between Child PHBS Behavior With Enterobiasis At Rt. 09/07 Susukan Village In East Jakarta And Its Review From The Islamic Perspective - Malsyah, Salsabella; Ndaru Andri Damayanti; Muhammad Arsyad; Rika Ferlianti (Junior Medical Journal, 2023)
Background: Enterobius vermicularis known as pinworms is an intestinal parasite that is disturbing and is still a public health problem worldwide, especially in children aged 6-10 years. Migration of female worms in the perianal area, especially at night, can disrupt children's sleep hours, and affect health in general. Methodology: The method used is quantitative with a cross sectional approach. Results: Examination results of 59 anal swab samples, 1,7% showed positive enterobiasis results. Filling in the child's PHBS behavior questionnaire, obtained from parental information and researchers' observations. Enteribiasis positive samples were found in pre-school children with poor PHBS behavior.Conclusion: Enterobiasis positive samples were found in pre-school children with poor PHBS behavior. Statistical tests showed that there was a significant correlation (p <0.05) in the incidence of enterobiasis with poor child PHBS behavior and Islamic teachings had an influence on the incidence of helminthiasis.